Gen Z and the Eucharist in the context of Maluku Protestant Church (GPM): A Liturgical Study - Kanidya Christandira Tuhumury; Ester Pudjo Widiasih (ARUMBAE: Jurnal Ilmiah Teologi dan Studi Agama, 2025)
This research examines the participation of Generation Z in the Eucharist and its implications for fostering peace within the context of the Protestant Church in the Mollucas (GPM). The background of this study is rooted in the social conflicts experienced in Maluku, which have impacted Generation Z and necessitate their preparation to avoid replicating the traumas of the past. Through the Eucharistic liturgy, this generation can discover the meaning of reconciliation and cultivate harmonious relationships with God, oneself, others, and the natural world. This research employs a mixed-method approach, combining qualitative and quantitative methodologies, and involves Generation Z from the Rehoboth and Ameth congregations. The focus of the study is on how Generation Z understands the meaning of the Eucharist, their participation in worship, and its effects on the preservation of peace in Maluku. The findings suggest that while Generation Z acknowledges the Eucharist as a sacred sacrament, the meanings and values it embodies are often not integrated into their daily lives. This study aims to formulate a contextual liturgy of the Eucharist that can respond to the voices and needs of Generation Z in creating peace as peace builders.